Cisco Packet Tracer Simulation as Effective Pedagogy in Computer Networking Course - Abdul Rashid, Nazre bin; bin Othman, Md. Zahar; bin Johan, Rasyidi; bin Hj. Sidek, Salman Firdaus (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The Computer Networking course commonly taught in mixed mode involving lecture and practical session whereas beside face-to-face theory session, students need to experience hands-on activities in order to appreciate the technology and contents. Nevertheless the abstraction in Computer Networking course such as the complexity in TCP/IP network layering, the connection and configuration of client and server’s framework, differences in static and dynamic IP address configuration had imposed a great challenge for students to understand and grab the main concept of computer networking technology. As such, an approach of using computer network simulation and visualization tool in teaching and learning Computer Networking course is seen beneficial for educators and students. In this research, computer network simulation software of CISCO Packet Tracer was utilized in Computer Networking (MTN3023) course. Students (N=55) were exposed to CISCO Packet Tracer on which they developed Wide Area Network (WAN) that consists of configuration activities of Personal Computer (PC), Servers and Switches according to CISCO standard. Subsequently, student’s feedback and their insight on the effectiveness of CISCO packet Tracer in learning computer networking were probed using questionnaire. All the feedbacks were investigating statistically using SPSS 16.0. From the analysis, the descriptive results shown that all students were agreed (N=32 : Strongly Agree; N=23 : Agree) that CISCO Packet Tracer had successfully help them to understand several key concepts of computer networking and at the same quash some abstractions they faced in the course. In a nutshell, CISCO Packet Tracer as a simulation and visualization tool had been proven to be an effective software in supporting the teaching and learning of computer networking course.